(untitled) (Annals of Medical Research, 2021)
Aim: To evaluate whether iodine density (ID) and normalized iodine density (NID) of tumor on rapid kV-switching dual energy CT is associated with histological parameters which influences disease prognosis in gastric cancerMaterial and Methods: Twenty patients with gastric adenocarcinoma who had preoperative staging CT imaging dual energy mode in arterial phase were retrospectively included. Patients who had neoadjuvant treatment prior to surgery were excluded. ID and NID values were measured on arterial phase dual energy CT images on a dedicated workstation.Results: ID and NID of the tumor were significantly lower in poorly differentiated tumors compared with well differentiated tumors (p=0.019, p=0.046), and also in patients with unfavorable histology compared with unfavorable histology group (p=0.005, p=0.042). There were no significant ID and NID value differences between patients with and without serosal infiltration, nodal metastasis, lymphovascular and perineural invasion, surgical margin involvement (p>0.05).Conclusion: ID related parameters can be useful for predicting the prognosis of gastric cancer.